New interaction model for the annular zone of stepped piles with respect to their vertical dynamic characteristics. (January 2020) - Wang, Ning; Le, Yi; Hu, Wentao; Fang, Tao; Zhu, Bitang; Geng, Daxin; Xu, Changjie
Abstract: Stepped piles with a larger section at the top have been increasingly used as foundations for bridge abutment in China. In this paper, numerical modelling using ABAQUS is firstly carried out to investigate the behavior of a annular zone below the top larger section. Then, a new interaction model with a wedge-shaped soil below the annular zone is proposed for pile–soil system. In the model, the soil wedge and normal pile segment were treated as a generalized pile segment. By combining the Novak plane strain model and Rayleigh-Love rod theory, the dynamic characteristics of a stepped pile subject to a vertical harmonic excitation at the pile head are theoretically investigated. The analytical solutions are deduced using Laplace transform and impedance function transfer method. The proposed model is verified by the sensitivity analysis of the soil wedge dimension and comparison with FEM results. Compared with the conventional Voigt model, the present solution shows a flatter oscillation in complex impedance curves, indicating that the Voigt model may overestimate the dynamic response of stepped piles. Finally, selected results are presented to examine the influence of pile geometry on the vertical dynamic responses.